A coupled elastic-plastic damage model for the mechanical behavior of three-dimensional (3D) braided composites. (22nd March 2018) - Ge, Jingran; He, Chunwang; Liang, Jun; Chen, Yanfei; Fang, Daining
Abstract: A coupled elastic-plastic damage model is developed to describe the non-linear mechanical behavior of three-dimensional (3D) braided composites. In this model, the fiber breakage, inter-fiber fracture and matrix fracture are considered in the level of the fiber bundle and matrix. The onset and propagation of fiber bundle failure mechanisms are elastic and brittle, which is accounted for elastic damage model, and the elastic-plastic damage model used to describe the degradation of matrix is non-linear with progressive damage and inelastic strains. A set of internal variables are introduced to characterize the damage states of the fiber bundle and matrix and as a subsequence the degradation of the material stiffness. The damage initiation and propagation criteria are based on the Hashin criteria for the fiber bundle and the von Mises yield criterion for the matrix. The proposed damage model is implemented in the non-linear finite element analysis code ABAQUS using a user-subroutine UMAT to determine the response behavior of 3D braided composites under quasi-static loading, and the numerical predictions are compared with experimental data. The results predicted by the proposed model agree well with the experiment.